find the value of the polynomial y2 -5y+6 at y=1
Answers
Answered by
35
Hello!
• p(y) = y² - 5y + 6
• p( 1 ) = ( 1 )² - 5( 1 ) + 6
⇒ 1 - 5 + 6
⇒ 1 + 1 ⇒ 2
Therefore,
![\boxed{\sf p( 1 ) : y^{2} - 5y + 6 = 2} \boxed{\sf p( 1 ) : y^{2} - 5y + 6 = 2}](https://tex.z-dn.net/?f=%5Cboxed%7B%5Csf+p%28+1+%29+%3A+y%5E%7B2%7D+-+5y+%2B+6+%3D+2%7D)
Cheers!
• p(y) = y² - 5y + 6
• p( 1 ) = ( 1 )² - 5( 1 ) + 6
⇒ 1 - 5 + 6
⇒ 1 + 1 ⇒ 2
Therefore,
Cheers!
Answered by
12
Step-by-step explanation:
if y =1 , then
ANSWER . 2
PLEASE MARK ME AS THE BRAINLIEST
Similar questions